Deubiquitinating Function of Ataxin-3: Insights from the Solution Structure of the Josephin Domain - Mao, Yuxin; Senic-Matuglia, Francesca; Di Fiore, Pier Paolo; Polo, Simona; Hodsdon, Michael E.; De Camilli, Pietro (Proceedings of the National Academy of Sciences - PNAS, 2005)
Spinocerebellar ataxia type 3 is a human neurodegenerative disease resulting from polyglutamine tract expansion. The affected protein, ataxin-3, which contains an N-terminal Josephin domain followed by tandem ubiquitin (Ub)-interacting motifs (UIMs) and a polyglutamine stretch, has been implicated in the function of the Ub proteasome system. NMR-based structural analysis has now revealed that the Josephin domain binds Ub and has a papain-like fold that is reminiscent of that of other deubiquitinases, despite primary sequence divergence but consistent with its deubiqutinating activity. Mutation of the catalytic Cys enhances the stability of a complex between ataxin-3 and polyubiquitinated proteins. This effect depends on the integrity of the UIM region, suggesting that the UIMs are bound to the substrate polyubiquitin during catalysis. We propose that ataxin-3 functions as a polyubiquitin chain-editing enzyme.